The mobile media reader - Kavoori, Anandam P.; Arceneaux, Noah, 1968- (Digital formations, 2012)
Portable phones are now miniature multi-media centers that can fit neatly in one's pocket, and media industries of all types are adapting content for these new platforms, or innovating entirely new forms. In the light of this explosive growth, this diverse collection of essays establishes conceptual, critical frameworks for evaluating the latest transformations of the media landscape. Some essays provide historical context, exploring older phenomena, while others unpack the behind-the-scenes- negotiations that determine what kinds of services are available to consumers of the latest technology. This book is a comprehensive road map, enabling examination of the social, cultural, and commercial implications of media that are available anywhere at any time.